2018
DOI: 10.1051/e3sconf/20185002003
|View full text |Cite
|
Sign up to set email alerts
|

Influencia del terroir en el perfil aromático de Tempranillo Blanco en la D.O.Ca. Rioja

Abstract: Resumen. En los vinos blancos el aroma es uno de los principales atributos de calidad, siendo los compuestos aportados por la uva los que determinan el perfil varietal. Tempranillo Blanco es una variedad derivada de Tempranillo Tinto por mutación natural, que desde el año 2008 está autorizada únicamente en la D.O.Ca. Rioja. Sus vinos manifiestan características organolépticas de alta calidad, con notas afrutadas y florales intensas. En este trabajo se estudió el perfil aromático varietal de Tempranillo Blanco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Several volatile compounds such as geranylacetone, mequinol, and eugenol were isolated from the spine grape from V. davidii, that have not been reported for other Vitis species, while (E,E)-2,4-hexadienal, which is not produced by V. vinifera, was also found in the spine grape in a wide concentration (Meng et al, 2013). Despite this differentiating attribute reported by these authors, the (E,E)-2,4-hexadienal has been found in grape berries from different V. vinifera grapevine varieties, such as Airén, Cabernet Sauvignon, Chardonnay, Kyoto, Macabeo, Sauvignon Vert and Tempranillo Blanco (García, Chacón, Martínez, & Izquierdo, 2003;González-Barreiro, Rial-Otero, Cancho-Grande, & Simal-Gándara, 2015;OuYang et al, 2015;Savoi et al, 2016;Martínez, Rubio-Bretón, Vicente, & García-Escudero, 2018;Wang et al, 2019). On the other hand, it was reported that C6 compounds were the predominant family of aromatic volatile compounds in most of the V. davidii spine grape clones, being trans-2-hexenal the most predominant (Meng et al, 2013).…”
Section: Vitis Davidiimentioning
confidence: 76%
“…Several volatile compounds such as geranylacetone, mequinol, and eugenol were isolated from the spine grape from V. davidii, that have not been reported for other Vitis species, while (E,E)-2,4-hexadienal, which is not produced by V. vinifera, was also found in the spine grape in a wide concentration (Meng et al, 2013). Despite this differentiating attribute reported by these authors, the (E,E)-2,4-hexadienal has been found in grape berries from different V. vinifera grapevine varieties, such as Airén, Cabernet Sauvignon, Chardonnay, Kyoto, Macabeo, Sauvignon Vert and Tempranillo Blanco (García, Chacón, Martínez, & Izquierdo, 2003;González-Barreiro, Rial-Otero, Cancho-Grande, & Simal-Gándara, 2015;OuYang et al, 2015;Savoi et al, 2016;Martínez, Rubio-Bretón, Vicente, & García-Escudero, 2018;Wang et al, 2019). On the other hand, it was reported that C6 compounds were the predominant family of aromatic volatile compounds in most of the V. davidii spine grape clones, being trans-2-hexenal the most predominant (Meng et al, 2013).…”
Section: Vitis Davidiimentioning
confidence: 76%
“…The aromatic compounds that come from the grape, also called varietal aromas, are directly related to the quality of the wine, and therefore to its value. The aromatic characterization of Spanish white grape varieties has been little studied, particularly that of Vitis vinifera L. Tempranillo Blanco . This grapevine variety is a natural mutation of Tempranillo, grown since 2008 only in the Appellation d’Origine Contrôlée (A.O.C.)…”
Section: Introductionmentioning
confidence: 99%
“…Rioja, and it is the second white variety (12%) grown in the A.O.C. Rioja in terms of surface area, after Viura (70%). …”
Section: Introductionmentioning
confidence: 99%
“…4 The aromatic characterization of Spanish white varieties has been little studied, 5 particularly that of Vitis vinifera L. Tempranillo Blanco. [6][7][8] This variety is a natural mutation of Vitis vinifera L. Tempranillo, and has been grown since 2008 only in the Appellation d'Origine Contrôlée (A.O.C.) Rioja.…”
Section: Introductionmentioning
confidence: 99%
“…Rioja in terms of surface area, after Vitis vinifera L. Macabeo (a. k. a. Viura) (70%). 6,7,9 The fact that it is an exclusive variety of the A.O.C. Rioja gives it a special value to the producing area and allows it to be differentiated from other regions.…”
Section: Introductionmentioning
confidence: 99%